Estabelecimento de condições para ensaio de dissolução de cápsulas de cinarizina empregando planejamento fatorial - Gehring, Patrícia Alves Franco; Santos, Olímpia Maria Martins; Pereira, Gislaine Ribeiro; Araújo, Magali Benjamim de; Bonfilio, Rudy [UNESP] (Sociedade Brasileira de Química, 2011)
This work describes the establishment of dissolution test conditions for 75 mg cinnarizine capsules using a multivariate approach. A 2³ full factorial design was carried out to achieve the best conditions and HCl 0.1 mol L-1 as dissolution medium, basket as apparatus at 100 rpm and collect time at 30 min were considered adequate. The quantification was carried out by spectrophotometry at 251 nm. Both dissolution procedure and analytical method were validated and all parameters were within the acceptable limits. Since there is no official monograph for this pharmaceutical product, this dissolution test could be applied for quality control routine.
Establishment of dissolution test conditions for cinnarizine in pharmaceutical capsules using factorial design
Keywords: dissolution test; cinnarizine; 2³ full factorial design